Humidity sensitive properties of paracetamol. (11th September 2019) - Wang, R J; Zhu, G B; Wang, C C
Abstract: A common coldrex, paracetamol, was used as humidity sensing material. The capacitance-type humidity sensor was fabricated by aerosol deposition method. The humidity sensitive properties were investigated through dielectric measurements. Our results reveal that the sensor has exciting performances in high relative humidity. Both −OH and −NH groups have contributions to water absorption. The −OH groups lead to a water-containing surface layer giving rise to pronounced Maxwell-Wagner response, which in turn, yields the humidity response that can be easily adjusted by an external electric field. This work indicates that the paracetamol is a promising humidity sensing material.